Tahap pengetahuan keselamatan pekerjaan dan faktor-faktor yang mempengaruhinya di Institut Latihan Kementerian Kesihatan Malaysia Zon Selatan - Isahari, Smile (2020)
Occupational safety and health (OSH) has recently become a rising issue in all industrial sectors in Malaysia. Nevertheless, Ministry of Health Training Institutes (ILKKM) are not exempted in from such issue as the staff as well as trainees are also exposed to occupational safety and health hazards. This study aims to identify the level of safety knowledge among the staff at the ILKKM Southern Region. Furthermore, the research identified the factors that could influence the level of safety knowledge. There are three factors studied in this research namely safety training, safety communication and safety rules & procedures. A quantitative study has been conducted on 217 staff of ILKKM in Johor, Negeri Sembilan and Melaka using self-administered questionnaires. The descriptive analysis results revealed that the level of occupational safety knowledge among the respondents is high. Moreover, the correlation analysis has indicated that there is positive and significant correlation between the independent variables and safety. In addition, the result of multiple regression analysis showed that safety training has significantly influenced safety knowledge of the ILKKM staff. In conclusion, this study has successfully identified that the level of safety knowledge among staff in ILKKM Southern Region is high and safety training is the dominant influencing factor. Continual further studies need to be conducted especially on other factors which might become the determinants for occupational safety knowledge in ILKKM.